Locally compact semi-algebras generated by a commuting operator family - N. R. Nandakumar; Cornelis V. Vandermee (International Journal of Mathematics and Mathematical Sciences)
Conditions are provided for the local compactness of the closed semi-algebra generated by a finite collection of commuting bounded linear operators with equibounded iterates in terms of their joint spectral properties.